Acoso escolar y la salud mental en los estudiantes de la Unidad Educativa Dr. Segundo Wong Mayorga - Cedeño Cedeño, Jennifer Esther (2019)
The bullying among adolescents has become a problematic situation in children and young people around the world, situation that comes to afflict various aspects of development such as the mental health of an individual, so that in the present investigation had as a general objective, to show the incidence of bullying in the mental health of the students in the unit education Dr. Segundo Wong Mayorga. This investigation is based on a study of learning style with qualitative and quantitative orientation, which manipulated scientific methods such as: i inductive –deductive and analytical-synthetic, supported in the use of techniques and instruments, such as the application of the You survey to focus groups, such as students, parents and teachers from the educational institution, for which we selected a sample of 190 people. In this research work can be located within the first chapter the problem raised, with an analysis of macro-level context, meso and micro, together with the rationale and objectives, both general and specific. In the second chapter is the theoretical framework detailing, both previous research and theoretical foundations of the studied variables. The third chapter is the results of the investigation of each of the variables represented by pictures and corresponding figures are. Finally it proposes a plan of psycho-education in order to reduce the rates of bullying and strengthen mental health in adolescents